Criminal Liability for Offenses Resulting from Errors of Autonomous Vehicles in the Kingdom of Saudi Arabia: A Comparative Study - Ali, Islam (Journal of Legal Sciences, 2025)
This study analyzes the criminal liability for crimes resulting from errors of self-driving vehicles in Saudi Arabia through a comparative approach assessing the adequacy of current legislation to cope with technological advancements. The descriptive-analytical method was applied by examining relevant local and international laws, as well as exploring legal perspectives on whether artificial intelligence could bear criminal liability or if responsibility should be assigned to manufacturers, programmers, or users. The findings reveal that the existing legal framework is insufficient, as it is built on the premise of a human actor, which makes it inadequate for addressing autonomous vehicles. The study recommends legislative amendments to define the roles of different parties clearly and to establish mechanisms that ensure accountability for crimes resulting from AI errors. It further suggests considering artificial intelligence as a legal entity under specific regulations to balance technological innovation with legal security.